2018
DOI: 10.1093/biolre/ioy063
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic infertility in women is associated with distinct changes in proliferative phase uterine fluid proteins†

Abstract: The regenerative, proliferative phase of a woman's menstrual cycle is a critical period which lays the foundation for the subsequent, receptive secretory phase. Although endometrial glands and their secretions are essential for embryo implantation and survival, the proliferative phase, when these glands form, has been rarely examined. We hypothesized that alterations in the secreted proteome of the endometrium of idiopathic infertile women would reflect a disturbance in proliferative phase endometrial regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Nevertheless, the primary epithelial cells used in adhesion assessment following hormonal treatment hold the characteristics of the parent tissue obtained from fertile or infertile women, i.e., capacity for sufficient or insufficient differentiation towards a potentially receptive phenotype. Thus, it appears that potential for the epithelium to subsequently develop receptivity is present even prior to ovulation [50,51]. Intriguingly, the data presented herein complement the findings of Sebastian-Leon et al [52] in which retrospective analysis of "receptivity" (window of implantation; WOI) predictions found that up to 76.6% of women with implantation failure had a pathological WOI or a pathological and displaced WOI.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, the primary epithelial cells used in adhesion assessment following hormonal treatment hold the characteristics of the parent tissue obtained from fertile or infertile women, i.e., capacity for sufficient or insufficient differentiation towards a potentially receptive phenotype. Thus, it appears that potential for the epithelium to subsequently develop receptivity is present even prior to ovulation [50,51]. Intriguingly, the data presented herein complement the findings of Sebastian-Leon et al [52] in which retrospective analysis of "receptivity" (window of implantation; WOI) predictions found that up to 76.6% of women with implantation failure had a pathological WOI or a pathological and displaced WOI.…”
Section: Discussionsupporting
confidence: 84%
“…DAVID‐based analysis revealed that pathways enriched in Ishikawa cells following Tsc‐sEV treatment (Figure 3C, Table 2, Table S11) include protein translation and localization [22,23,117,118] (module 1 and 3) (translation initiation/elongation factors, ribosomal subunits), immune regulation [24,119] (module 2), antioxidant activity [120,121] (module 4, 8), cell‐matrix adhesion and laminin binding [101] (module 12, 16), NAD metabolism [122] (module 18), cadherin binding (module 20) [90,91]; processes that are dynamically regulated at the site of implantation. On the other hand, pathways underrepresented in recipient cells include DNA replication and elongation (module 5) [123,124], carbon metabolism (TCA cycle) (module 11, 17), actin cytoskeleton organisation (module 14, 15), and oxidoreductase activity (module 19) (Figure 3D, Table S11).…”
Section: Resultsmentioning
confidence: 99%
“…The enrichment for specific biological processes of genes that formed new negative connections was clear evidence of the biological relevance of these new connections. Notably, among genes annotated with proteolytic activity, ADAM19 43 , ASRGL1 44 , ATG4B 45 , DPEP2 46 , IMMP2L 47 , PSMB9 48 , SERPINE2 49 , UCHL3 50 , USP42 51 have been implicated in female infertility. A more drastic change in patterns of coexpression was observed with the inversion of gene connections (significant pairwise coexpression in one group with significant coexpression with opposite direction in another group).…”
Section: Discussionmentioning
confidence: 99%